Reverse sequence polymerization-induced self-assembly in aqueous media: a counter-intuitive approach to sterically-stabilized diblock copolymer nano-objects. Issue 42 (11th October 2022) - Penfold, Nicholas J. W.; Neal, Thomas J.; Plait, Corentin; Leigh, Andrew E.; Chimonides, Gwen; Smallridge, Mark J.; Armes, Steven P.
Abstract : A 500 nm charge-stabilized latex is converted into 40 nm sterically-stabilized nanoparticles via reverse sequence polymerization-induced self-assembly (PISA). Abstract : Polymerization-induced self-assembly (PISA) is a powerful platform technology for the efficient synthesis of block copolymer nanoparticles in many types of solvents, including water. In PISA, a soluble precursor block is used to grow a second insoluble block, which leads to in situ self-assembly of the block copolymer chains. Thus, in the case of aqueous PISA, the water-soluble block is always prepared first because this confers steric stabilization. Herein, we challenge this paradigm by demonstrating that amphiphilic diblock copolymer chains can be prepared in water by preparing the hydrophobic block first via reversible addition–fragmentation chain transfer (RAFT) polymerization. This counter-intuitive reverse sequence PISA formulation utilizes an ionic RAFT agent to conduct the RAFT aqueous dispersion polymerization of 2-hydroxypropyl methacrylate (HPMA), which results in the formation of charge-stabilized PHPMA latex particles of ∼500 nm diameter. Initial attempts to chain-extend these hydrophobic PHPMA chains with water-miscible monomers such as glycerol monomethacrylate (GMA) were unsuccessful, with only uncontrolled free radical polymerization being observed in the aqueous phase. However, using a water-immiscible monomer such as isopropylideneglycerol methacrylate (IPGMA) enabled the synthesis of charge-stabilized PHPMA-PIPGMA latex particles. Subsequent acid hydrolysis of the PIPGMA block led to the in situ formation of sterically-stabilized PHPMA-PGMA diblock copolymer spheres. Alternatively, dissolution of the precursor PHPMA latex in a methanol/water binary mixture enables RAFT solution polymerization of water-miscible monomers such as GMA or N, N ′-dimethylacrylamide (DMAC) to be achieved with good control. The resulting amphiphilic diblock copolymer chains then undergo self-assembly in aqueous solution after removal of the methanol co-solvent. Finally, this reverse sequence PISA protocol can also be applied to other vinyl monomers such as 2-methoxyethyl methacrylate (MOEMA) or diacetone acrylamide (DAAM), which significantly broadens its scope.